Humans as a service : the promise and perils of work in the gig economy - Prassl, Jeremias (OXFORD, 2018)
Is crowdsourcing the future of work? This book offers a lively and critical account of the gig economy: its promises and realities, what is at stake, and how we can ensure that customers, workers, platforms, and society at large benefit from this global and growing phenomenon.